2002
DOI: 10.1038/sj.bmt.1703732
|View full text |Cite
|
Sign up to set email alerts
|

Prospective evaluation of Candida species colonization in hospitalized cancer patients: impact on short-term survival in recipients of marrow transplantation and patients with hematological malignancies

Abstract: Summary:Most hematogenous candidiasis originates from endogenous host flora. The impact of clinically prominent Candida colonization on short-term mortality (р14 weeks) was prospectively studied in 193 hospitalized patients from 1998 to 1999. Clinically prominent colonization included yeasts isolated from all sterile body sites and Ͼ50 colonies of Candida from non-sterile sites. Fourteen (7.1%) patients were granulocytopenic (ANC р100/ l). Nineteen (9.8%) had undergone marrow transplantation, 26 (13.5%) had a … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
23
0
1

Year Published

2002
2002
2023
2023

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 35 publications
(24 citation statements)
references
References 29 publications
0
23
0
1
Order By: Relevance
“…14 However, a rise in colonization and bloodstream infections due to fluconazole-resistant species has been reported in neutropenic patients receiving fluconazole prophylaxis. [15][16][17] Furthermore, the emergence of C. albicans isolates with reduced susceptibility to fluconazole has been described in the course of long-term, low-dose exposure to fluconazole. 18 Interestingly in this context, molecular-relatedness studies have shown that multiple C. albicans sub-populations with distinct antifungal susceptibility patterns can coexist in patients with human immunodeficiency virus infection presenting with oral candidiasis.…”
Section: Introductionmentioning
confidence: 99%
“…14 However, a rise in colonization and bloodstream infections due to fluconazole-resistant species has been reported in neutropenic patients receiving fluconazole prophylaxis. [15][16][17] Furthermore, the emergence of C. albicans isolates with reduced susceptibility to fluconazole has been described in the course of long-term, low-dose exposure to fluconazole. 18 Interestingly in this context, molecular-relatedness studies have shown that multiple C. albicans sub-populations with distinct antifungal susceptibility patterns can coexist in patients with human immunodeficiency virus infection presenting with oral candidiasis.…”
Section: Introductionmentioning
confidence: 99%
“…The variations in the rates of antifungal susceptibility among C. glabrata isolates from patients at hospitals within a geographic area are not known, however. In addition, since systemic C. glabrata yeast infections frequently arise from the host's endogenous microflora, mainly that in the orointestinal and genitourinary tracts (21,25,26), we thought that it was important to assess the antifungal susceptibility profiles of both colonizing C. glabrata strains and those associated with systemic disease. During a 12-month period, C. glabrata organisms isolated from patients receiving treatment at three urban teaching hospitals in New York City were evaluated prospectively.…”
mentioning
confidence: 99%
“…Moreover, an earlier report on bleomycin showed that in vitro activities do not always match in vivo activities [32]; hence, the results of our study need to be confirmed in an animal model. Neutropenic patients with advanced cancers and malignancies are at a high risk for developing invasive and superficial Candida infections [33,34]. Most of the time, C. albicans is associated with these infections and is a reason for the high mortality rates in cancer patients [35,36,37].…”
Section: Discussionmentioning
confidence: 99%